AKSENTUISI MODERASI BERAGAMA DALAM LINGKUNGAN KELUARGA SEJAK DINI - Farida, Yusmar; Oktavia, Syeri (STAI Darul Qalam Tangerang, 2023)
Indonesia is a pluralistic country consisting of different tribes, races and religions, so tolerance is needed in understanding all the differences that exist, as well as cultural educational institutions whose citizens are also diverse. Therefore, religious moderation is very appropriate to be applied in the life of the nation and state, especially in multicultural societies. Religious moderation is a middle way in dealing with differences in both extreme and fundamental groups. The family context in strengthening religious moderation is a top priority compared to the social and educational context. Likewise in the research context, the theme of the method of developing religious moderation values ​​in the family context is still very limited. Therefore, this study aims to explore the results of research on this theme to map the research that has been done and opportunities for future researchers. This research is a library research based on books and previous research. The results show that research on the method of developing religious moderation values ​​in the family is still limited in terms of the number of studies, the variety of methods, and the type of research used. The implications of these findings are discussed further